2021
DOI: 10.1186/s12882-021-02516-6
|View full text |Cite|
|
Sign up to set email alerts
|

Does conservative kidney management offer a quantity or quality of life benefit compared to dialysis? A systematic review

Abstract: Background Patients with stage 5 chronic kidney disease (CKD5) collaborate with their clinicians when choosing their future treatment modality. Most elderly patients with CKD5 may only have two treatment options: dialysis or conservative kidney management (CKM). The objective of this systematic review was to investigate whether CKM offers a quantity or quality of life benefit compared to dialysis for some patients with CKD5. Methods The databases M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 52 publications
2
19
0
1
Order By: Relevance
“…One of the distinct benefits afforded by conservative kidney management is that patients who choose this option experience less intensive care near the end of life than patients who receive dialysis. 6,22,30,42,43,51 However, it also is recognized that patients who forgo dialysis receive hospice services less often and die in the hospital setting more often than other patients in the same health system but with other serious illness, such as terminal cancer. 51 More research is needed to understand and overcome the barriers to supportive care for this population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the distinct benefits afforded by conservative kidney management is that patients who choose this option experience less intensive care near the end of life than patients who receive dialysis. 6,22,30,42,43,51 However, it also is recognized that patients who forgo dialysis receive hospice services less often and die in the hospital setting more often than other patients in the same health system but with other serious illness, such as terminal cancer. 51 More research is needed to understand and overcome the barriers to supportive care for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Toward this end, several systematic reviews and meta-analyses [3][4][5][6][7] have been conducted comparing outcomes between patients treated with dialysis and those treated conservatively. They show that dialysis is associated with longer survival compared with conservative approaches [3][4][5][6] but that these survival advantages are attenuated with increasing age and comorbidity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 46 A recent systematic review found that CKM may be associated with improved quality of life and lower symptom burden and hospitalization. 47 Of note, the intended purpose of this review is not so much to make a direct head-to-head comparison of dialysis versus CKM but rather to illustrate the potential expected life trajectory of an older individual with advanced CKD managed either conservatively or with a dialysis pathway. It is clear that not all patients are suitable for or will benefit from kidney replacement therapy, particularly in those who are frail or highly comorbid.…”
Section: Patient Preferencesmentioning
confidence: 99%